2013
DOI: 10.1088/0031-8949/88/05/057001
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘Discussion on novel attractive force between ions in quantum plasmas—failure of simulations based on a density functional approach’

Abstract: In a recent article [P.K. Shukla, B. Eliasson and M. Akbari-Moghanjoughi, Physica Scripta 87, 018202 (2013)] the authors criticized our analysis of the screened proton potential in dense hydrogen that was based on ab initio density functional theory (DFT) simulations [M. Bonitz, E. Pehlke, and T. Schoof, Phys. Rev. E 87, 037102 (2013)]. In particular, they attributed the absence of the Shukla-Eliasson attractive force between protons in the DFT simulations to a failure of DFT. Here we discuss in detail their a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The existence of such an attractive potential betweens ions of similar charge has been the subject of intense recent debate. [49][50][51][52][53] However, the long-range structure of the SE electrostatic potential can be oscillatory (Friedel Oscillations). The cohesive properties of ions inside degenerate free electron gas can beautifully describe the metallic binding.…”
Section: Friedel Oscillations and Shukla-eliasson Potentialmentioning
confidence: 99%
“…The existence of such an attractive potential betweens ions of similar charge has been the subject of intense recent debate. [49][50][51][52][53] However, the long-range structure of the SE electrostatic potential can be oscillatory (Friedel Oscillations). The cohesive properties of ions inside degenerate free electron gas can beautifully describe the metallic binding.…”
Section: Friedel Oscillations and Shukla-eliasson Potentialmentioning
confidence: 99%
“…Thus our results clearly confirm the recent explanations given in Refs. [30,31] of the invalidity of linearized QHD for the problem of ions in streaming quantum plasmas.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an even simpler approach that is based on a quantum hydrodynamic model (QHD) has been applied that predicts an attractive interaction between ions even in the absence of streaming, u e = 0 [29]. Comparisons with density functional theory revealed that this is incorrect [30] and points to limitations of QHD models for dense plasmas [31,32]. A recent overview and more references can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Note also that the single potential (19) with the given parameters in (6) is valid for both potential forms of monotonic and oscillatory. Because of discrepancy between the above result and the density functional theory (DFT) simulations an intense debate has gone on the validity of the hydrodynamic or DFT theories [57][58][59][60][61][62]. This is because the SE potential gives rise to the Lennard-Jones type attractive potential around the screened ion for a wide range of the electron number density which is well above the metallic density regime.…”
Section: Static Charge Screeningmentioning
confidence: 99%